Analysis of Meter Registry Uncertainty. Issue 9 (1st September 2016) - Sumrak, McKenna L.; Johnson, Michael C.; Barfuss, Steven L.
Abstract : This study was conducted to quantify the effects of uncertainty on residential water meter registry testing and to demonstrate how to calculate registry uncertainty. All measurements have random and systematic errors, and understanding those errors is important to properly assess the limitations of the test. For this study, registry uncertainty calculations were computed according to the American Society of Mechanical Engineers (ASME) Test Uncertainty Manual (2006) for volumetric and gravimetric scale test setups. Because of possible errors, uncertainties in the registry results may be high enough to justify passing some meters that fail and failing some meters that pass. In such cases, increasing the volume of water collected to higher than AWWA minimum standards reduces uncertainty and provides more relevant results. This study shows that uncertainties are significant and should be computed in order to accurately analyze the results.